Inflation and Asset Prices in an Exchange Economy - Danthine, Jean-Pierre; Donaldson, John B. (Econometrica, 1986)
[This paper studies the pricing of common stocks in the context of a monetary, rational expectations equilibrium. Special attention is given to the relationship between inflation and asset returns.]